STRIVING FOR GETTING BACHELOR OF DOCTOR IN ROBERTS LUKETICS’ 21: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - KWINTOKO, TULUS (2010)
This study concerns with the movie entitled 21 which is directed by Robert Lucketic. The analysis of this research paper is focused on the major character, Ben Campbell, based on structural elements and psychological perspective. In analyzing the psychological aspect, the researcher applied the theory of Individual Psychology proposed by Alfred Adler. This research belongs to qualitative research, which employs textual data. The textual data are taken from the movie itself as primary data source and the other materials which are related to the analysis as secondary data source. There are two findings of this study. Firstly, the structural elements of movie present a unity. It appears in the exposition, complication, climax, and resolution of the story. Secondly, the individual psychological analysis shows the struggle of Ben Campbell for getting bachelor of doctor.